Configuraciones de la construcción colaborativa docente de retos de aprendizaje vinculados al territorio - Claro Espejo, Natalia (2022)
The objective of this study aims to understand the configuration of the collaborative teaching construction of learning challenges linked to the territory from the analysis of cases of two educational institutions in peri-urban areas of Metropolitan Lima. It is framed within the research line of diversity, interculturality and curriculum. The chosen educational institutions are located in two different districts of Lima. One of them has a small student population, belonging to families with a lower-middle economic stratum; the other has a medium-sized population belonging to families of low and medium-low economic stratum. The study was carried out from a qualitative approach with a sample of four secondary school teachers. Interviews were applied to the teachers, as well as the analysis of their curricular documents. It was found that in the first educational institution teachers have more potential to propose learning challenges linked to the territory, however none of the educational institutions manages to do it from the development of competencies and complex thinking, as is proposed by the National Curriculum. It is concluded that there are a number of aspects that influence this process. One of those is about the unable for the tacher to relate local challenges to other dimensions or scales, limiting offering complex learning experiences. The development of a critical reflective teaching practice could open a complex understanding of the contexts in which its students live to generate learning proposals that point to the transformation of reality from active citizen participation.